The association between prior statin usage and long-term outcomes after critical care admission - Beed, Martin; Brindley, P.G.; Mahajan, Ravi P.; Juttner, I.; Campion-Smith, Jo; Wilson, Vince (Elsevier, 2016)
Background: Statins may have immunomodulatory effects that benefit critically ill patients. Therefore we retrospectively examined the association between survival and the prescription of statins prior to admission to an intensive care unit (ICU), or high dependency unit (HDU), as a result of major elective surgery, or as an emergency with a presumed diagnosis of sepsis. Methods: We retrospectively studied critical care patients (ICU or HDU) from a tertiary referral UK teaching hospital. Nottingham University Hospitals has over 2200 beds, of which 39 are critical care beds. Over a five-year period (2000–2005) 414 patients were identified with a presumed diagnosis of sepsis, and 672 patients were identified with a planned ICU/HDU admission following elective major surgery. Patients prescribed statins prior to hospital admission were compared with those who were not. Demographics, past medical history, drug history, and Acute Physiology and Chronic Health Evaluation II (APACHE II) scores were examined. Univariate and multivariate analyses were applied using the primary endpoint of survival at five years after admission. Results: Patients prescribed statins prior to critical care admission were, on average, older, with higher initial APACHE II scores and more pre-existing comorbidities. Statins were almost invariably stopped following admission to critical care. Statin usage was not associated with significantly altered survival during hospital admission, or at five years, for either patients with sepsis (9% v 15%, P=0.121; 73% v 84%, P=0.503 respectively), or post-operative patients (55% v 58%, P=0.762; 57% v 63%, P=0.390). Conclusions: Prior statin usage was not associated with improved or worsening outcomes in patients admitted to critical care after elective surgical cases or with a presumed diagnosis of sepsis.